An Overview of Nutrient Budgets for Use in Nutrient Management Planning - Amy L. Shober; George Hochmuth; Christine Wiese (EDIS, 2011)
For professionals responsible for ensuring water quality, this 4-page fact sheet describes the types and limitations of nutrient budgets. Written by Amy L. Shober, George Hochmuth, and Christine Wiese, and published by the UF Department of Soil and Water Science, November 2011.